Recycling of waste printed circuit boards into ion exchange resin. Issue 3 (5th December 2014) - Zhang, Jianqiu; Tian, Tao; Chen, Jinyang; Zu, Jianhua; Wang, Yangjun
Abstract : Ion exchange resins with high IEC and stability are obtained from WPCBs by treatment with sulphuric acid. Abstract : Recycling the nonmetal components of waste printed circuit boards (WPCBs), mainly thermosetting epoxy resins (TEPRs), is quite difficult because they are insoluble and inflexible. We report a new method to convert TEPRs into ion exchange resin by treatment with sulphuric acid and the equilibrium ion exchange capacity (IEC) of the produced sample is 1.63 meq g −1 . FTIR indicated that TEPRs were modified by sulphuric acid and X-ray photoelectron spectroscopy (XPS) verified that sulfonic acid group (–SO3 − ) was introduced. The produced ion exchange resin was stable up to 200 °C by TG-DTG analysis. The maximum adsorption capacities for Cu(ii ) and Ca(ii ) were 23.30 and 56.27 mg g −1, respectively. The Langmuir model gave a better fit for adsorption than the Freundlich model. The activation energies ( E a ) were 21.18 and 48.53 kJ mol −1 for Cu(ii ) and Ca(ii ), respectively, with pseudo-second-order kinetics.